Respuesta :
Answer:
No
Step-by-step explanation:
Let's solve your equation step-by-step.
−2x−6=2x+6
Step 1: Subtract 2x from both sides.
−2x−6−2x=2x+6−2x
−4x−6=6
Step 2: Add 6 to both sides.
−4x−6+6=6+6
−4x=12
Step 3: Divide both sides by -4.
−4x/−4 = 12/-4
=
x=−3
Answer:
This equation have solution.
Step-by-step explanation:
1) Add 2x to both sides.
[tex] - 6 = 2x + 6 + 2x[/tex]
2) Simplify 2x + 6 + 2x to 4x + 6.
[tex] - 6 = 4x + 6[/tex]
3) Subtract 6 from both sides.
[tex] - 6 - 6 = 4x[/tex]
4) Simplify -6-6 to -12.
[tex] - 12 = 4x[/tex]
5) Divide both sides by 4.
[tex] - \frac{12}{4} = x[/tex]
6) Simplify 12/4 to 3.
[tex] - 3 = x[/tex]
7)Switch sides.
[tex] x = - 3[/tex]
Therefor, this equation has solution. and the solution is, x = -3.